Estimated Fluorinated Compounds Exposure from Waterproof Eye Cosmetics Use in Women of Reproductive Age - Nadia Zerlinda; Fitratul Ilahi; Husna Yetti; Eka Nofita; Kemala Sayuti (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Waterproof eye cosmetic are currently trending because they are a great choice for consumers who want to get long-lasting products. Research on fluorinated compounds has found high levels of fluorine in products advertised as 'wear-resistant' or 'long-lasting. Exposure to PFAS is found to cause immune suppression, liver disease, cancer, decreased fertility and low birth weight. This study aimed to determine the exposure to fluorinated compounds through the use of waterproof eye cosmetics in women of childbearing age. This study was conducted from October to December 2023. The study sample amounted to 334 women consisting of 101 high school students, 127 college students, and 106 bank employees spread across the provinces of West Sumatra, Riau, and West Java, data were obtained by filling out a 73-items research questionnaire. The results showed that the frequency of use of waterproof eye cosmetics in the last 6 months was different for each respondent group. 90% of the respondents used mascara. Silicones compounds, acrylates, and color additives were the most common compounds found in the ingredients of the waterproof eye cosmetics used by the respondents. The highest estimated systemic exposure dose of per and polyfluoroalkyl substances (PFAS) compounds was found in high school student respondents with an average of 0,22 x 10-7 kg/BW/day followed by bank employees (0,15 x 10-7kg/BW/day) and collage student (0,14 x 10-7 kg/BW/day. It can be concluded that the rate of use of waterproof eye cosmetics is high in women of reproductive and high school students have a greater potential to be exposed to fluorinated compounds.